2020
DOI: 10.1186/s12889-020-09218-y
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child communication about sexual issues in Zambia: a cross sectional study of adolescent girls and their parents

Abstract: Background: Parent-child communication about sexual issues can reduce risky sexual behaviour amongst adolescents. Risky sexual behaviour is of concern in sub-Saharan Africa where the prevalence of early pregnancy, unsafe abortion and HIV are high. Parent-child communication about sexual issues presents a feasible approach for reducing sexual risk amongst adolescents in sub-Saharan Africa but limited research exists from the region. This study from Zambia examines the sociodemographic and psychosocial factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
3
12
1
Order By: Relevance
“…Although adolescents and young women have better access to sexual health information through their parents, primarily their mothers, whom they can dialogue with about sexuality and sexual experiences (Measor, 2015), this study found that men were more included in the transmission of knowledge within their respective families. The study's results match with that of Isaksen and collaborators (Isaksen et al, 2020) who found that less than half of the girls had spoken with their parents about romantic and/or sexual issues, but that proximity through family connection was a key factor for obtaining information. Parents play a key role in deciding when their children begin engaging in sexual intercourse, impeding early sexual activity (França & Frio, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Although adolescents and young women have better access to sexual health information through their parents, primarily their mothers, whom they can dialogue with about sexuality and sexual experiences (Measor, 2015), this study found that men were more included in the transmission of knowledge within their respective families. The study's results match with that of Isaksen and collaborators (Isaksen et al, 2020) who found that less than half of the girls had spoken with their parents about romantic and/or sexual issues, but that proximity through family connection was a key factor for obtaining information. Parents play a key role in deciding when their children begin engaging in sexual intercourse, impeding early sexual activity (França & Frio, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, parent-child communication about sexual issues and contraception use is averted when parents feel uncomfortable and fear as they would perpetuate their own early sexual practices and negative attitudes towards contraception. 47,48 Therefore, given the potential that parentchild communication about sexual issues may have in reducing adolescent sexual risk, 47,49 the findings suggest the efforts to increase parent-child communication may benefit from using open communication with neutral messages and appearing comfortable to display positive attitudes towards communication around sex and contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individuals who report that their family members approve of premarital sex were more likely to experience UIP. Therefore, students' family members, especially their parents must be involved in educational programs to foster their values related to responsible sexual behavior and wise decision making [21][22][23][24]. An optimal family centered approach is expected to create an environment where parents communicate with their adolescent children about sexual issues more frequently and with greater ease [21][22][23][24].…”
Section: Implications Of the Studymentioning
confidence: 99%